Microstructure and electrical properties of AZO films prepared by RF magnetron sputtering - Bakri, Jufriadi; Sutjipto, Agus Geter Edy; Othman, Raihan; Muhida, Riza (Trans Tech Publications, Switzerland, 2011)
AZO is an ideal replacement transparent conducting oxide (TCO) for ITO to all corresponding applications. The typical applications include: transparent electrodes for solar cells, flat panel displays, LCD electrodes, electro-magnetic compatibility (RF-EMI shielding) coatings, touch panel transparent contacts, static discharge dissipation. The production of useful and commercially attractive thin films using different deposition processes is very important parameter to investigate. A systematic study of the sputtering condition and their influenced on electrical and structural were studied. In this work, AZO films were deposited by RF magnetron sputtering at 200 °C. The result shows that the deposited time has influenced the characteristic of deposited AZO films. For a longer deposition time, thin film shows a uniform grain growth. The resistivity found minimum at the deposition time of 45 minutes. It can be considered that by reducing of the grain boundaries which enable the electron carries to conduct smoothly.